Knowledge, attitudes and preventive behaviors related to dengue vector breeding control measures among adults in communities of Vientiane, capital of the Lao PDR - Chanthalay Sayavong; Jiraporn Chompikul; Somsak Wongsawass; Cheerwit Rattanapan (Elsevier, 2015)
Summary: This research aimed to determine the knowledge, attitudes and preventive behaviors (KAP) of adults in relation to dengue vector control measures in the communities of Vientiane, the capital of the Lao PDR. A total of 207 respondents were actively participating in this cross-sectional descriptive study in 2011. Representatives of households were interviewed face-to-face by six trained interviewers using a structured questionnaire. KAP reliabilities of 0.89, 0.91 and 0.95 were reported in the pilot sample of 30 cases. The associations between each independent variable and prevention behavior were tested with chi-square tests. Multiple logistic regression was used to determine the factors that were significantly associated with preventive behavior while controlling for the other variables. The results revealed that 51.69% of the respondents had a high level of knowledge. More than 94% of the respondents knew that dengue fever is a dangerous communicable disease and that dengue fever is transmitted from person to person via mosquitoes. More than half (56.52%) of the participants had positive attitudes toward vector control measures, and 52.17% exhibited a high level of preventive behavior in terms of dengue vector control measures. Preventive behaviors were significantly associated with information provided from sources that included health personnel (p = 0.038) and heads of villages (p = 0.031) and with knowledge levels (p < 0.001). This study suggests that proactive health education through appropriated mass media and community clean-up campaigns should strengthen and encourage community participation, particularly in terms of addressing mosquito larvae in overlooked places, such as the participants' own homes, for example, in flower vases and ant traps. Keywords: Knowledge, Attitude, Preventive behavior, Dengue vector, Community